Os sintagmas nominais do inglês: um estudo comparativo de corpus entre o uso de determinantes nas produções escritas de falantes nativos do inglês e aprendizes brasileiros - Vanessa Cristina Oliveira Wright (2014)
The objective of this research was to investigate how Brazilian learners produce determiners in noun phrases of English language in academic writing, and to compare them with English native speakersdeterminers produced in academic writing. We base this work in the fact that each group of speakers present their own identity, since mother language may also influence in the production of the secondlanguage. The results found showed that the learners, in fact, presented their own characteristics in their production. However, not all these differences were based on the influence of the second language. Thelearners produced less complex noun phrases than the native speakers, and also produced determiners with less variety of lexical items. Most differences do not consist in mistakes, it just indicatespreferences and tendencies of this group of English speaking learners. As done by other researches based on corpus of apprentices, it was verified the need to continue studies based on learners corpora.To come to these conclusions, the collected data were organized in charts, organized and analized by using the corpus linguistics tool WordSmith, and the corpora LOCNESS and BR-ICLE.